Strain engineering in AlGaN/GaN HEMTs for performance enhancement. (26th May 2020) - Mohapatra, E.; Nanda, R.K.; Das, S.; Dash, T.P.; Jena, J.; Dey, S.; Maiti, C.K.
In the first part of this work, using TCAD simulations, we examine the breakdown voltage as a function of field plate geometry. In the second part, we show that field plate-based GaN HEMT structures can be optimised to have effectively reduced undesirable parasitic capacitances to greatly improve both the high transconductance and current gain cut-off frequency simultaneously. We report a new generation of high performance AlGaN/GaN HEMTs grown on high resistivity SiC substrates. We examine the small signal and large signal device performances against technological parameters such as the gate length, field plate length, and the source-drain contact separation. The device with a gate length of 0.25 μm and field plate length of 0.3 μm exhibits a maximum dc drain current density of 3.66 A/mm at VGS = 3 V with an extrinsic transconductance of 233.6 mS/mm and an extrinsic current gain cut-off frequency ( ft ) of 78.9 GHz.